Pemodelan Gedung Kuliah Bersama Politeknik Negeri Lampung Menggunakan Building Information Modeling (BIM) - Anggraini, Tiara; Husni, Hasti Riakara; Bayzoni, Bayzoni; Ashruri, Ashruri (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
Building Information Modeling (BIM) is one of the technologies that can present information about building elements through 3D modeling. One of the BIM software that can be used to model buildings in 3D is Autodesk Revit. The purpose of this research is to model the Joint Lecture Building of Lampung State Polytechnic in 3D by applying the BIM concept to obtain the volume of work as a reference for making decisions when operational and maintenance will be carried out and comparing the results obtained with the existing Bill of Quantity (BoQ). The data used in this research refers to the as plan drawing. The modeling process involves setting units, creating grids and levels, creating structural families and modeling them, creating architectural families and modeling them, entering identity data, conducting clash checks, and then issuing the volume of work. This research produces the volume of work on wall paint, doors, windows, tiles (ceramic/granite), and ceilings with scenarios in the form of volume for each room on each floor. Based on the results of this research, it can be concluded that modeling the Joint Lecture Building of Lampung State Polytechnic using the BIM concept with Autodesk Revit 2023 software is a more effective and efficient method because the volume output obtained is not only comprehensive but can be specialized on certain floors or rooms.Key words : Building Information Modeling (BIM), Autodesk Revit, operational and maintenance